SOME SOCIAL FACTORS IN THE FORMATION OF SEVERE PNEUMONIA IN YOUNG CHILDREN - Gofurov Zhavlonbek Abduvakhobovich; Khudaiberdieva Khamrokhon Tilavodievna; Kosimov Dilmurod Sirojiddinovich (Scholar Express Journals, 2023)
It was possible to assess some social factors in the formation of severe pneumonia in young children
Keywords: pneumoniaI; socio-hygienic factor; terial and living conditions in the family